2021
DOI: 10.1371/journal.pone.0253044
|View full text |Cite
|
Sign up to set email alerts
|

Validation and psychometric properties of the Brazilian-Portuguese dispositional flow scale 2 (DFS-BR)

Abstract: Introduction: Flow state is a psychological concept used to describe the optimal engagement in different activities. Therefore, the DFS-2 has been developed as an instrument to measure an individual’s dispositional tendency to flow state as a personality trait. Objective: Aiming to obtain an adapted version of the DFS-2 for the Brazilian-Portuguese language (DFS-BR) and for general activities, we performed its forward- and backward-translation, and we validated it. Methods: After gathering answers from 681 Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
(67 reference statements)
0
12
0
3
Order By: Relevance
“…However, the AVE of the EM_AT was 0.33, which indicated that about 67 percent of the variance of the EM_AT's items was due to the measurement error instead of be captured by the EM_AT itself (Fornell & Larcker, 1981). Since the unacceptable AVE of the EM_AT was 0.33, we may conclude that the convergent validity of the EM_AT was adequate based only on its CR of 0.745 (Fornell & Larcker, 1981;Malhotra, 2020; previous studies e.g., Leuteritz et al, 2019;Bittencourt et al, 2021).…”
Section: B) Phi Coefficient Of Inter-dimension Correlationmentioning
confidence: 77%
See 2 more Smart Citations
“…However, the AVE of the EM_AT was 0.33, which indicated that about 67 percent of the variance of the EM_AT's items was due to the measurement error instead of be captured by the EM_AT itself (Fornell & Larcker, 1981). Since the unacceptable AVE of the EM_AT was 0.33, we may conclude that the convergent validity of the EM_AT was adequate based only on its CR of 0.745 (Fornell & Larcker, 1981;Malhotra, 2020; previous studies e.g., Leuteritz et al, 2019;Bittencourt et al, 2021).…”
Section: B) Phi Coefficient Of Inter-dimension Correlationmentioning
confidence: 77%
“…In Indonesia, the recent studies (e.g., Handayati et al, 2020;Saptono et al, 2020;Wardana et al, 2020) report the results of the validation of the adapted EM scale. Based on this, we followed a guideline from Bittencourt et al (2021) which examined how many dimensions of EM have been validated by such studies. However, such studies validated the adapted EM scale based only on one dimension (i.e., inadequate dimension).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow measure was obtained using a questionnaire containing 26 questions according to Bittencourt et al ( 2021 ). The validation results for this scale indicate good fit (X2-df = 2.94, CFI = 0.98, TLI = 0.97 and RMSEA = 0.053).…”
Section: Methodsmentioning
confidence: 99%
“…4. Dispositional Flow State (DFS) [42]; Brazilian version [43]. This instrument assesses an athlete's perception of several indicators of predisposition to the flow state.…”
Section: Instrumentsmentioning
confidence: 99%